A Review of Key Technologies Development of Super High-Rise Building Construction in China. (17th January 2022) - Gong, Jian; Fang, Tingchen; Zuo, Junqing
Abstract : Super high-rise building is a typical architectural form of urban modernization, and it is also the trend of urban architectural development. This paper reviews the development history of super high-rise buildings in China combined with the engineering practice of representative super high-rise buildings since the 1980s, such as the Shanghai Center, Shanghai Oriental Pearl Tower, Jinmao Tower, Shanghai World Financial Center, Canton Tower, and Shanghai Tower. The development process of the key technologies of super high-rise projects from the aspects of several technologies, such as soft soil pile foundation and foundation pit technology, concrete structure construction technology, integral formwork equipment technology, and steel structure comprehensive installation technology, is also elaborated. At the same time, the Shanghai Tower is selected as a typical case to share the innovative technology of China's tallest building. Finally, prospects for development of super high-rise construction technology are presented.